2015
DOI: 10.1142/s0192415x15500846
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Increases Doxorubicin Sensitivity by Suppressing STAT3 in Lung Cancer

Abstract: Berberine (BBR), an alkaloid component isolated from Chinese medicinal herb Huang Lian, has aroused broad interests for its antitumor effect in recent years. The signal transducer and activator of transcription 3 (STAT3), plays critical roles in malignant transformation and progression and was found to be constitutively activated in a variety of human cancers. In this study, we show that BBR inhibited cell proliferation, induced apoptosis, and suppressed tumor spheroid formation of lung cancer cell lines. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…Berberine also suppresses the invasive and metastasis of nasopharyngeal carcinoma (NPC) by inhibiting the activation of Signal Transducer and Activator of Transcription 3 (STAT3), a key mediator to trigger tumor-promoting inflammation [23]. The similar actions were observed in lung cancer, of which cell proliferation and tumor spheroid formation were suppressed by berberine [24]. Notably, berberine exhibits selective cytotoxicity against cancer cells instead of normal hepatocytes [25].…”
Section: Representative Anticancer Hcd Herbsmentioning
confidence: 99%
“…Berberine also suppresses the invasive and metastasis of nasopharyngeal carcinoma (NPC) by inhibiting the activation of Signal Transducer and Activator of Transcription 3 (STAT3), a key mediator to trigger tumor-promoting inflammation [23]. The similar actions were observed in lung cancer, of which cell proliferation and tumor spheroid formation were suppressed by berberine [24]. Notably, berberine exhibits selective cytotoxicity against cancer cells instead of normal hepatocytes [25].…”
Section: Representative Anticancer Hcd Herbsmentioning
confidence: 99%
“…As berberine is also known for its action on STAT3, [12][13][14] the effect of berberine on STAT3 signaling was further explored. The Western blot analyses of STAT3 and pSTAT3 (tyrosine (Tyr) 705, and Ser 727) were performed in CCA cells treated with berberine in comparison with the control cells.…”
Section: Berberine Inhibited Growth Of Cca Cell Linesmentioning
confidence: 99%
“…Clinical studies have found that doxorubicin in combination with other chemotherapeutic drugs acts as a treatment for lung carcinoma (9). In general, the efficacy of chemotherapeutic drugs is limited in the treatment of lung cancer and the carcinoma cells may readily develop resistance to the drugs in clinical practice, significantly reducing the therapeutic efficacy of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%